Ag/polyaniline/reduced graphene polyester conductive fabric with enhanced electromagnetic shielding performance. Issue 1 (February 2021) - Xie, Xiangyu; Chen, Zhuoming; Xin, Binjie
Abstract: The Ag/polyaniline/reduced graphene composite fabric is fabricated via chemical insitu polymerization to adsorb a layer of polyaniline and graphene on the polyester fabric, and then Ag is plated on the fabric surface using magnetron sputtering. The electromagnetic shielding performance of composite fabrics was studied at different concentrations of aniline and graphene, and the influence of magnetron sputtering power and time on fabric performance was further studied. At the same time, the Ag/polyaniline/reduced graphene polyester composite conductive fabric was characterized by Fourier transform infrared spectroscopy (FTIR) and scanning electron microscope (SEM). It was found that when the concentration of polyaniline was 0.7mol/L and the concentration of graphene was 0.15mol/L, the electrical conductivity and electromagnetic shielding performance of the composite fabric came to the best under controlled sputtering power of 200W and time of 20 minutes.